The Cost of Mating: Influences of Life History Traits and Mating Strategies on Lifespan in Two Closely Related Yponomeuta Species - Bakker, A. C.; Campos Louçã, J.; Roessingh, P.; Menken, S. B. J. (International Journal of Zoology, 2011)
Theory predicts that in monandrous butterfly species males should not invest in a long lifespan because receptive females quickly disappear from the mating population. In polyandrous species, however, it pays for males to invest in longevity, which increases the number of mating opportunities and thus reproductive fitness. We tested an extension of this idea and compared male and female lifespan of two closely related Yponomeuta species with different degree of polyandry. Our results confirmed the theoretical prediction that male lifespan is fine-tuned to female receptive lifespan; once-mated males and females of both polyandrous species had an equal lifespan. However, the degree of polyandry was not reflected in male relative to female lifespan. The observed similar female and male lifespan could largely be attributed to a dramatic reduction of female lifespan after mating.